Efektivitas Kombinasi Slow Sand Filter Media Geotekstil dan Karbon Aktif untuk Menyisihkan Nilai Permanganat dan Total Coliform - Sherly Galuh Puspita; Firra Rosariawari; Okik Hendriyanto Cahyonugroho; Aussie Amalia (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
The water of Kali Jagir, Surabaya, used as a raw water source, has been contaminated with high levels of BOD, COD, and permanganate. Therefore, this research seeks to address these issues by combining slow sand filtration with various media, including geotekstil and activated carbon. The study aims to optimize this combination in reducing parameters such as permanganate and total coliform in the raw water. The research methodology includes literature review, testing of raw water characteristics, preparation of slow sand filter reactors, preparation of filter media, and testing of media variations with an observation of organic and bacteriological pollutant removal efficiency. The results show that the combination of filter media involving sand, activated carbon, and geotekstil is effective in reducing organic pollutants. Geotekstil aids in the growth of the schmutzdecke layer and facilitates cleaning, while sand and activated carbon tend not to support such growth. Moreover, the optimum schmutzdecke growth time varies depending on the type of media used. These findings have significant implications for raw water treatment in industrial areas vulnerable to pollution, resulting in quality drinking water and addressing the frequent clogging issues in slow sand filters.